Mixing Taylor shifts and universal Taylor series. (24th December 2014) - Beise, H.‐P.; Meyrath, T.; Müller, J.
Abstract : It is known that, generically, Taylor series of functions holomorphic in a simply connected complex domain exhibit maximal erratic behaviour outside the domain (so‐called universality) and overconvergence in parts of the domain. Our aim is to show how the theory of universal Taylor series can be put into the framework of linear dynamics. This leads to a unified approach to universality and overconvergence and yields new insight into the boundary behaviour of Taylor series.